2021
DOI: 10.3390/ijms221910576
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Posttranslational Modification in Pathogenesis of Rheumatoid Arthritis: Focusing on Citrullination, Carbamylation, and Acetylation

Abstract: Rheumatoid arthritis (RA) is caused by prolonged periodic interactions between genetic, environmental, and immunologic factors. Posttranslational modifications (PTMs) such as citrullination, carbamylation, and acetylation are correlated with the pathogenesis of RA. PTM and cell death mechanisms such as apoptosis, autophagy, NETosis, leukotoxic hypercitrullination (LTH), and necrosis are related to each other and induce autoantigenicity. Certain microbial infections, such as those caused by Porphyromonasgingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 283 publications
(331 reference statements)
0
34
0
Order By: Relevance
“…Multiple studies have demonstrated that elevated ACPA levels are present in preclinical RA, and the presence of ACPA is highly specific for predicting the future development of RA, with a specificity of 85-95% and a sensitivity of 67% [66][67][68]. Therefore, ACPAs have been included in the widely used ACR/EULAR 2010 classification criteria [20].…”
Section: Autoantibody Productionmentioning
confidence: 99%
“…Multiple studies have demonstrated that elevated ACPA levels are present in preclinical RA, and the presence of ACPA is highly specific for predicting the future development of RA, with a specificity of 85-95% and a sensitivity of 67% [66][67][68]. Therefore, ACPAs have been included in the widely used ACR/EULAR 2010 classification criteria [20].…”
Section: Autoantibody Productionmentioning
confidence: 99%
“…Regarding Aa, the presence of Ab directed against the LPS of Aa, serotype B, or against its virulence factor, leukotoxin B, have been further reported in RA [ 5 ]. The release of leukotoxin A is effective in inducing neutrophil extracellular traps (NETs) that possess plenty of citrullinated histones and DNA such that the NETs are able to engulf the bacteria in order to prevent Aa dissemination [ 32 , 33 , 34 ]. As a consequence, ACPA capacity to recognize bacterial membrane antigens provides an explanation to our report that ACPA detection is associated with a reduction of Porphyromonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other protein modifications such as aberrant glicosilation may also participate in the activation of the immuno-response in RA. Genetics, including epigenetics and environmental factors such as smoking or infections (periodontitis), seem to have relevant implications in protein modifications and, consequently, in the initiation of the altered immuno-response in RA [2,3,31].…”
Section: Discussionmentioning
confidence: 99%
“…RA is characterized by the presence of autoantibodies that are of paramount importance for the diagnosis and prognosis of the disease and have been implicated in its pathogenesis. In recent years, significant advances in the diagnosis and management of RA have changed the prognosis and outcome of RA for a significant proportion of patients [1][2][3].…”
Section: Introductionmentioning
confidence: 99%